Análisis crítico del tema de la violencia en La vorágine de José Eustasio Rivera. (2014)
La Vortágine is a famous novel of the Colombian and Latin American literature which deals singularly with the issue of violence. This paper proposes a novel philosophical reflection to address violence as an object of knowledge. First, a new approach from literary theory arises, then, aspects of the story are considered, such as the dual nature of the world, the absurd and self-productive dynamics of violence and, with the help of several authors, we find how these same aspects support new approaches. This article leads us to think of new ways of being and acting in the world from the way we relate to the other.